LEGAL IMPLICATIONS OF BREAST MILK DONATION ON THE LACTASHARE PLATFORM PERSPECTIVE OF SADD AL-DZARI’AH - Anjani, Ria; Bachri, Syabbul (Universitas Islam Negeri Mataram, 2025)
The advancement of digital platforms has led to innovations such as breast milk donation through Lactashare. While this addresses nutritional needs for infants, it raises complex legal issues, particularly in Islamic jurisprudence regarding lineage and mahram relationships. This study examines the legal implications of breast milk donation from the perspective of Sadd al-Dzari’ah, a principle in Islamic law that emphasizes harm prevention. Utilizing a qualitative case study design, the research draws from in-depth interviews with the founder of Lactashare and relevant legal documents to explore how the institution navigates regulatory, ethical, and religious challenges. The study applies thematic analysis to examine the procedural safeguards, identity verification systems, and legal documentation practices, particularly the issuance of mahram certificates and donor-recipient records. The findings reveal that while Lactashare implements various safeguards in line with Islamic principles, such as donor screening, recording mahram certificates, and compliance with fatwas, it still faces challenges in completely preventing legal ambiguity regarding milk kinship, especially in areas outside Malang and Jakarta where monitoring is limited to online reporting, these risks are possible but uncertain and are likely to be outweighed by significant benefits to infant health especially in Indonesia, where stunting and infant mortality rates are high. This study contributes to Lactashare’s ability to anticipate these risks with a digital tracking system, the appointment of regional coordinators, intensive education, and strengthening regulations through legal agreements. Collaboration with local health and religious institutions is also expected to enhance supervision and legal protection. However, this study has limitations. It only focuses on the perspectives of Lactashare founders and legal documents, so further study is needed to capture the experiences and views of other stakeholders, such as donors, recipients, health professionals, and religious scholars. Despite these limitations, this work provides fundamental insights for policymakers, religious authorities, and digital health platforms on how to align technological innovation with Sharia law using the Sadd al-Dzari’ah framework.